Parental nutritional awareness of their preschool children at private preschools in Taman Scientex, Pasir Gudang, Johor. - Yusof, Nur Amalia Shafika Mohd (Universiti Sains Malaysia, 2024)
Nutrient is a substance that provides essential nourishment for growth and health. Nutrients are crucial for energy production, cell repair, and keeping the immune system strong. Nutritional awareness among parents is very important because it directly influences their children's dietary habits and overall health. The study aims to assess the parental nutritional awareness of their preschool children at private preschools in Taman Scientex, Pasir Gudang, Johor. A cross-sectional study was conducted on parents who have children aged four to six years old. Data was collected using a self-administered questionnaire adapted from Halder & Kejriwal (2016). A total of 190 parents from private preschools at Taman Scientex, Pasir Gudang, and Johor who fulfilled the inclusion and exclusion criteria were involved in this study. They were selected through a probability simple random sampling method. Data collected were statistically analysed using the SPSS software version 27. The study used descriptive statistics and the Fisher’s Exact Test. The results show that 119 (62.6%) of participants have a good level of awareness of nutritional. There was an association between sociodemographic data [level of education (p=0.003), household income (p=0.02) and children’s BMI (p=0.003) ] with parental nutritional awareness. In conclusion, parental nutritional awareness helps identify gaps in knowledge and practices, enabling interventions to improve children's eating habits. This promotes healthy nutrition, prevents obesity, malnutrition, and developmental delays, contributing to the long-term well-being of children.